The Dynamics of Mycoplasma gallisepticum Nucleoid Structure at the Exponential and Stationary Growth Phases - Fisunov, Gleb Y.; Zubov, Alexander I.; Pobeguts, Olga V.; Varizhuk, Anna M.; Galyamina, Mariya A.; Evsyutina, Daria V.; Semashko, Tatiana A.; Manuvera, Valentin A.; Kovalchuk, Sergey I.; Ziganshin, Rustam K.; Barinov, Nicolay A.; Klinov, Dmitry V.; et al. (Frontiers in Microbiology, 2021)
The structure and dynamics of bacterial nucleoids play important roles in regulating gene expression. Bacteria of class Mollicutes and, in particular, mycoplasmas feature extremely reduced genomes. They lack multiple structural proteins of the nucleoid, as well as regulators of gene expression. We studied the organization of Mycoplasma gallisepticum nucleoids in the stationary and exponential growth phases at the structural and protein levels. The growth phase transition results in the structural reorganization of M. gallisepticum nucleoid. In particular, it undergoes condensation and changes in the protein content. The observed changes corroborate with the previously identified global rearrangement of the transcriptional landscape in this bacterium during the growth phase transition. In addition, we identified that the glycolytic enzyme enolase functions as a nucleoid structural protein in this bacterium. It is capable of non-specific DNA binding and can form fibril-like complexes with DNA.